PENGARUH GREEN MARKETING, BRAND IMAGE DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN AIR MINUM DALAM KEMASAN AQUA PADA MAHASISWA DI YOGYAKARTA - Tri Aji Wibowo; Sri Ekanti Sabardini (Bajang Institute, 2024)
This research aims to analyze the influence of the Green Marketing, Brand Image and Price Perception variables on purchasing decisions. This research method is a quantitative method with the number of samples used being 100 students in Yogyakarta who have purchased Aqua brand AMDK. The sampling technique uses the Non-probability Sampling model. The method used is the Purposive Sampling method. The tests used in this research are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, t test and coefficient of determination test. The results of this research show that: 1) The Green Marketing variable has a positive and significant effect on Purchasing Decisions, 2) The Brand Image variable has a positive and significant effect on Purchasing Decisions, 3) The Price Perception variable has no effect on Purchasing Decisions. Based on testing the coefficient of determination (adjusted R2) shows a result of 0.595 (59.5%), which means that the Green Marketing, Brand Image and Price Perception variables contribute an influence of 59% to the Purchasing Decision variable, while the remaining 40.5% is explained by other variables not included in this study.